2006
DOI: 10.1111/j.1095-8312.2006.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Gestation temperature affects sexual phenotype, morphology, locomotor performance, and growth of neonatal brown forest skinks, Sphenomorphus indicus

Abstract: We maintained pregnant Sphenomorphus indicus under four thermal conditions for the whole gestation period to assess the effects of gestation temperature on offspring phenotypes. Parturition occurred between late June and early August, with females at high body temperatures giving birth earlier than those maintained at low body temperatures. Litter size, litter mass, and postpartum body mass did not differ among treatments, and females with relatively higher fecundity produced smaller offspring. Females gave bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 40 publications
5
29
0
3
Order By: Relevance
“…For example, males have longer tails than females of the same SVL in E. prezwalskii (the present study) and Podarcis muralis (common wall lizard; Braña and Ji 2000) but not in Eremias argus (Mongolian racerunner; Hao et al 2006) and Takydromus septentrionalis (northern grass lizard; Du and Ji 2006). Consistent with studies of other viviparous lizards (Schwarzkopf and Shine 1991;Shine and Harlow 1993;Wapstra 2000;Ji et al 2006Ji et al , 2007, the results of this study show that maternal thermal regimes affect gestation length but not litter size in E. prezwalskii. Females provided with longer basking opportunity had earlier parturition dates than did females provided with shorter basking opportunity (Table 1).…”
Section: Discussionsupporting
confidence: 89%
“…For example, males have longer tails than females of the same SVL in E. prezwalskii (the present study) and Podarcis muralis (common wall lizard; Braña and Ji 2000) but not in Eremias argus (Mongolian racerunner; Hao et al 2006) and Takydromus septentrionalis (northern grass lizard; Du and Ji 2006). Consistent with studies of other viviparous lizards (Schwarzkopf and Shine 1991;Shine and Harlow 1993;Wapstra 2000;Ji et al 2006Ji et al , 2007, the results of this study show that maternal thermal regimes affect gestation length but not litter size in E. prezwalskii. Females provided with longer basking opportunity had earlier parturition dates than did females provided with shorter basking opportunity (Table 1).…”
Section: Discussionsupporting
confidence: 89%
“…For example, within scincid and agamid lizards, increased maternal basking (in viviparous species) or incubation temperature (in oviparous species) shifts offspring sex ratios in Niveoscincus ocellatus (Wapstra et al 2004, Bassiana duperreyi (Radder et al 2008), Amphibolurus muricatus, and Chlamydosaurus kingii (Harlow and Shine 1999), but not in Pseudemoia pagenstescheri (Shine and Downes 1999), Egernia whitii (While et al 2009), or Lampropholis guinchenoti (Qualls and Shine 1998). Asian scincid species show similar diversity, with incubation temperature affecting offspring sex ratio in Sphenomorphus indicus (Ji et al 2006a) but not in Mabuya multifasciata (Ji et al 2006b). A recent field study on the oviparous B. duperreyi (Telemeco et al 2009) showed that females of this species have adjusted both seasonal timing of oviposition and nest depth in response to rising ambient temperatures, but have been unable to compensate entirely for climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although reduced thermal opportunity during pregnancy often increases gestation length in lizards, consistent effects on offspring running speed and/or size are not apparent (e.g. Ji et al, 2006;Li et al, 2009;Cadby et al, 2014), and for a skink with asynchronous births, differences in running speed between first-and last-born offspring within a litter were not consistent across the birth season (While et al, 2009a). Extended gestation or delayed parturition can also have negative consequences (e.g.…”
Section: Introductionmentioning
confidence: 99%